High dynamic range InP HBT delta-sigma analog-to-digital converters. - Inerfield, M. (IEEE Journal of solid state circuits)
To date, the development of multifunction multicarrier digital receivers for cellular base station and military communications applications has been limited by the demanding dynamic range requirements for the analog-to-digital converter (ADC). The use of oversampling delta-sigma modulators provides a promising approach to overcoming the dynamic range barriers Nyquist-rate converters face in the same applications. This paper discusses issues involved in the design of high-speed high dynamic range wide-band delta-sigma ADCs for such communications applications. Test results of prototype designs are also presented. The delta-sigma modulators described in this paper operate at sampling frequencies ranging from 1 to 2.5 GHz with center frequencies ranging from dc to 100 MHz, providing between 74 and 84.2 dB signal-to-noise ratio (12 and 13.7 bits) for bandwidths of 25 and 12.5 MHz, respectively. The loop filters are continuous-time low-pass and bandpass implementations of order 6 and 10, and were fabricated in an InP heterojunction bipolar (HBT) technology. A typical tenth-order design consumes 6 W of power and occupies a die area of 23.5 mm2.